Fiqh Al-Muwatanah: Nahdlatul Ulama's Interpretation About Citizenship - Muh. Sholihuddin (Millah: Journal of Religious Studies, 2021)
This article examines the influence and challenges of fiqh al-muwatanah in Indonesia. The discussion of this article focuses on a description of the pros and cons of the al-muwatinun concept offered by Nahdlatul Ulama (NU) and the challenges faced in implementing it. The method used is a literature study with a historical and comparative approach, then analyzed using content analysis. The research findings show that al-muwatinun as a socio-political concept is a new term that will not be found in the treasures of classical Islamic thought. Al-muwatinun is a product of NU ulama's ijtihad as a response to the strengthening of takfiri in Indonesia. Al-muwatinun contains values and teachings about equality, justice, and equality is a continuation of the mission brought by al-muwatinun to form a tolerant and peaceful society by eliminating the mention of infidels non-Muslims. All Indonesian people have the same status, whether Muslim or non-Muslim, and there is no majority or minority. Al-muwatinun is a form of fiqh typical of the archipelago. This idea has been started by previous Muslim thinkers who tried to contextualize Islamic law in Indonesia. On the other hand, the al-muwatinun concept shows NU's consistency in guarding the Unitary State of the Republic of Indonesia (NKRI).